Immediate effects of spinal manipulation in pain and global joint mobility in patients with chronic nonspecific low back pain - Fernandes, Walkyria Vilas Boas; Pizzol, Franciéli Dall; Capote, Andrielle Elaine; Melo, Sibele de Andrade; Schleder, Juliana Carvalho (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Objective: The aim of this study was to analyze the immediate effects of applying a manipulative intervention on chronic non-specific back pain and increasing global joint mobility. Method: A cross-sectional, randomized, single-blind study was carried out, consisting of 19 women aged between 18 and 55 years old, separated into two groups: Experimental Group (EG = 10) and Control Group (CG=9). The evaluation consisted of a physical examination, Rolland Morris questionnaire, fingertip-to-floor test, Visual Analogue Scale (VAS), and pressure algometry (L5) before and after the manipulative intervention. The EG was submitted to five vertebral manipulations, two in the bilateral pelvis region, one in the middle thoracic region (T5-T7) and two in the bilateral cervical region at the C3 level. The CG was submitted to two placebos manipulative techniques, being positioned in right and left lateral decubitus position for 10 seconds each, in the same position of global pelvic manipulation, but without the manipulative impulse (thrust). Results: The results were statistically significant in the EG in the reduction of sensation of pain (p<0,001) and the increase of overall joint mobility (p<0,05) when comparing pre and post intragroup moments. There were no statistically significant differences in relation to pain threshold evaluated in pressure algometry. Conclusion: It is concluded that a manipulative intervention is able to reduce the pain and to increase the global mobility immediately after its accomplishment.